Correlation Between Serum 25-Hydroxyvitamin D Levels in Albuminuria Progression of Diabetic Kidney Disease and Underlying Mechanisms By Bioinformatics Analysis - Huang, Bin; Wen, Wenjie; Ye, Shandong (Frontiers in Endocrinology, 2022)
Aim This study aimed to assess the correlation between serum 25-hydroxyvitamin D levels and albuminuria progression of diabetic kidney disease (DKD) and to use bioinformatics methods to determine the potential mechanism in the pathological process of advanced DKD. Methods A total of 178 type 1 diabetes mellitus (T1DM) patients with microalbuminuria complications who were hospitalized at least twice (with an interval > 24 months) were included in this study. We divided the patients into DKD progression (N=44) and stable group (N=134) on the basis of urinary albumin-to-creatinine ratio (UACR) by at least two randomized measurements. Stable group was defined as UACR between 30 and 300 mg/g, whereas progression group was defined as UACR >300 mg/g at the end of follow-up. The dataset GSE142025 from GEO was downloaded. After stratification by the median-centered log2 VDR expression value, the 21 advanced DKD samples were divided into two groups. The CIBERSORT algorithm was applied to calculate the infiltrated immune cells in advanced kidney tissues. Results 1) A multivariate Cox regression analysis revealed that DR (diabetic retinopathy), eGFR (estimated glomerular filtration rate), and 25-hydroxyvitamin D were significant independent predictors of DKD progression. 2) Kaplan–Meier survival curves of DKD progression by serum 25-hydroxyvitamin D stratification showed that the G2 and G3 groups were significantly different when compared with the G1 group. 3) There was a weak negative correlation between 25-hydroxyvitamin D level and UACR at baseline. 4) The high expression of VDR group was most positively correlated with enriched gene sets like reactome innate immune system and reactome G alpha I signalling events when compared with the low expression of VDR group. 5) The CIBERSORT algorithm showed decreased M2 macrophage infiltration in advanced kidneys in comparison to low VDR expression and high VDR expression. Conclusion This study concluded that low 25-hydroxyvitamin D levels can predict an increased risk of DKD albuminuria progression. Decreased M2 macrophage infiltration may be a potential mechanism involved in this pathogenesis.